Use of previous maternal health services has a limited role in reattendance for skilled institutional delivery: cross-sectional survey in Northwest Ethiopia - Kebede, Bekana (Dove Medical Press, 2013)
BACKGROUND: Maternal mortality rates are unacceptably high in Ethiopia. Institutional delivery with skilled care of the mother is one of the interventions proven to reduce the risk of complications that can cause maternal and neonatal mortality. Quality of service given during antenatal visits and childbirth are important measures. The purpose of this study was to investigate the use of skilled institutional delivery and its repeat use during a subsequent pregnancy and to identify any reasons why women avoid institutional delivery. METHODS: A community-based cross-sectional study was conducted from March to June 2012 in Chilga Woreda, Northwest Ethiopia. Data were collected from women who gave birth during the year preceding the survey. Information was entered and cleaned using the Statistical Package for Social Sciences. Multivariate and binary logistic regression was used to identify the relative effect of each explanatory variable on the outcome. RESULTS: A total of 402 (84.2%) women gave birth at home. Previous experience of skilled institutional delivery had a limited role in subsequent acceptance or use of institutional delivery. Most mothers who had previously had institutional delivery gave birth at home. Although 111 (40.8%) women visited the health facility during their pregnancy only because of illness, 184 (38.8%) did not know when to visit for antenatal care. In multivariate analysis, lower maternal education, being a rural resident, previous use of institutional delivery, remoteness of the health facility, and multiparity were factors significantly associated with less likelihood of institutional delivery. Number of months pregnant at the time of the first antenatal visit had no role in increasing the likelihood of institutional delivery. CONCLUSION: The quality of the obstetric services presently available for women living in Ethiopia needs review.